Experimental study on polymer fibre included sustainable pervious concrete - Jayanthi R., A.; Deepak M. S., B.; Mahendran K., C.; Surendar M., D. (International Journal of Engineering and Technology, 2019)
An experimental study on relationship between hardened concrete properties and rate of infiltration of polymer fibre included sustainable pervious concrete has been performed and presented in this paper. In this study, two different coarse aggregate sizes (20mm-10mm and 10mm-4.75mm) and varying percentage of polypropylene fibre included in the concrete mix (0.25%, 0.50%, 0.75%, 1.00%, 1.25%, 1.5%, 1.75% and 2.00%) were considered as parameters. The very little quantity of fine aggregate required in the design mix was replaced by graded bottom ash. A nominal design mix proportion for M30 grade of concrete was assumed as mean target strength. The engineering properties of plain pervious concrete and fibre included pervious concrete were compared with conventional concrete properties. In this study, all the pervious concrete specimens reached above 60% of the target strength. Based on the test results it was found that the using larger size of coarse aggregates in the concrete mix shows increases infiltration capacity but decrease in bond strength properties. Pervious concrete which was made using smaller size aggregates exhibited higher strength but lower infiltration capacity. The optimum fibre content that supports in enhanced strength and appropriate infiltration capacity was 1.5% in the design mix. This study evaluates relationship between the aggregate sizes and properties of fibre included pervious concrete. The results prove that it is possible to produce sustainable pervious concrete with good strength and acceptable infiltration capacity using coarse aggregate of size 20mm-4.75mm along with 1.5% polypropylene fibre addition.Â